Development of bio-medical & cosmetic products from keratin protein:the production of anti aging cream with UV protection from chicken feathers - Siti Nur Khairunisa, Mohd Amir (2012)
A research entitled the development of biomedical and cosmetic products from keratin protein. Protein builds up most of the outer surface on human body. In this research, chickens feathers will be used as protein sources. Hence, the protein in the chicken feather is extracted and used in the personal care products. The personal care products focused in this research is anti aging cream with ultra violet (UV) protection. The production of anti aging cream is using formulation created by safe and cheap ingredients easily available in Malaysia. The cream is then analyzed with pH meter, micro centrifuge, particle size analysis, rheometer, phase separation and tested with rat skin. All the data collected shows the creams are stable, no phase separations happen to cream and no irritation on the ratskin. In conclusion, there is no harm and safe in the usage of this anti aging cream with UV protection.